Moving Toward Effective Teacher Empowerment through Improved Decision Making at a Secondary School in Wyoming - Mayeski, Fran. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
A project to increase group decision making at a Wyoming secondary school is described in this practicum report. The intervention was designed to improve the group decision-making skills of members of the faculty advisory council and of department chairs. A skill development model based on training, practicing, monitoring, receiving feedback, and coaching was developed. Significant gains, as measured by the z test of proportions, were made in faculty acceptance of group decisions and in identification of decision-making processes before taking action. Chi square analysis that compared consistency in articulating role expectations before and after intervention indicated significant improvement. Department chairs who did not participate in the model regressed in their assumptions of task initiation functions. Another outcome was a significant improvement in the faculty's perception of the principal's effectiveness on the self-evaluation tool that originally had been a primary indicator of the need for intervention. Nineteen tables and 35 figures are included. Appendices contain journal entries, correspondence, interview notes, and survey responses. (70 references) (LMI)
ERIC Note: Requirement for Ed.D. degree, Nova University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collegiality; Decision Making Skills; Evaluation Utilization; High Schools; Participative Decision Making; Problem Solving; Professional Development; Teacher Participation; Wyoming; Reports, Research